2021
DOI: 10.3390/atmos12020227
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty of Rate of Change in Korean Future Rainfall Extremes Using Non-Stationary GEV Model

Abstract: Interest in future rainfall extremes is increasing, but the lack of consistency in the future rainfall extremes outputs simulated in climate models increases the difficulty of establishing climate change adaptation measures for floods. In this study, a methodology is proposed to investigate future rainfall extremes using future surface air temperature (SAT) or dew point temperature (DPT). The non-stationarity of rainfall extremes is reflected through non-stationary frequency analysis using SAT or DPT as a co-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Nonstationary impacts in terms of nonstationary return level for extreme precipitation may increase in the twenty-first century. Moreover, Aziz et al, [61] showed more consistent nonstationarity effects for temperature extremes at seasonal and annual scales from historical to future times. The investigation of historic-based analysis may only be helpful for short-run strategy and decision-making, while analysis based upon both historical and projected data may be more suitable for long-term strategy planning.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Nonstationary impacts in terms of nonstationary return level for extreme precipitation may increase in the twenty-first century. Moreover, Aziz et al, [61] showed more consistent nonstationarity effects for temperature extremes at seasonal and annual scales from historical to future times. The investigation of historic-based analysis may only be helpful for short-run strategy and decision-making, while analysis based upon both historical and projected data may be more suitable for long-term strategy planning.…”
Section: Discussionmentioning
confidence: 94%
“…The four distributions of generalized extreme value, Gumbel, normal, and lognormal, have been used in this study to carry out the return level for a specific return period. Numerous researchers used these probability distributions for the analysis of return levels of hydro-meteorological variables [39][40][41][60][61][62][63][64]. The analysis of precipitation was carried out for the historical and projected period.…”
Section: Stationary and Nonstationary Frequency Analysismentioning
confidence: 99%
“…Comparing the minimum and maximum ranges of each parameter after applying the non-informative priors reduces the variance. This method has been validated in previous studies conducted by (Jerez et al, 2021;Seo et al, 2021). The effect of make-up water parameters, such as sodium, chloride, and conductivity, influences the system conductivity.…”
Section: Discussionmentioning
confidence: 96%
“…Da states that specialists might assist the DM in discretizing in flood severity levels, in which probability density functions (PDFs) can be used to calculate . From this perspective, the Generalized Extreme Value (GEV) distribution is suitable to model extreme events, as observed in Esteves (2013) and Seo et al (2021);…”
Section: Risk Identification On Shelter Project's Locationmentioning
confidence: 99%